(untitled) (Research, Society and Development, 2020)
This study aims to estimate the surface runoff coefficient in the drainage area of the Bolonha and Água Preta lakes located in the municipalities of Belém and Ananindeua, State of Pará. To do so, we initially used images from a Digital Elevation Model (MDE). Shuttle Radar Topography Mission (SRTM); With the aid of ArcGIS® 10.5 geoprocessing software, the areas were quantified and the land use and occupation classification was performed. Thus, the runoff coefficient was estimated by values found in the literature and by the NRCS method, using as basis a local equation of heavy rainfall and Curve Number (CN) values for the discrimination of the areas in 2018. Therefore, this The results of the research, by the NRCS method, C values ranging from 0.169 to 0.321 were reached, depending on the return period of the local precipitation in a range from 1 to 150 years. The drainage area of the lakes Bologna and Água Preta has good infiltration, characteristic of rural areas, although it has 28.8% of already urbanized area. In conclusion, this work provides the academic environment with the updating of the Bologna and Água Preta lakes drainage sub-basin as a convergent drainage area, aiming to serve as a database and information for future academic works.